Access to oral care is a human rights issue: a community action report from the Downtown Eastside of Vancouver, Canada - Ehsan Jozaghi; Vandu; Russ Maynard; Yasaman Khoshnoudian; Mario A. Brondani (BMC, 2022)
Abstract To offer a critical reflection on an impoverished neighborhood in Vancouver, Canada, and their access to oral health care. A review of how a lack of publicly funded oral health care affects the most vulnerable, uninsured, and underserved citizens is performed. Personal and professional accounts on how entrepreneurial innovations of not-for-profit organizations can help to close the gap in access to oral health care are offered using the Vancouver Area Network of drug users (VANDU) and the PHS Community Services Society as case studies in British Columbia. Despite the efforts put forward by not-for-profit organizations such as the VANDU and the PHS Community Services Society, a national oral health care plan is warranted though still not a political imperative. Underserved citizens have a right to oral health care that is compassionate, collaborative, accessible, and affordable.